Use of a continuous positive airways pressure device for awake open shoulder surgery in a patient with obstructive sleep apnoea. Issue 2 (13th September 2016) - Chhaniyara, Puja; Hewson, David; Bedforth, Nigel
Summary: A 59‐year‐old male with severe obstructive sleep apnoea (OSA), a body mass index (BMI) of 46, and a predicted difficult airway was scheduled for open left shoulder rotator cuff repair. After preoperative multidisciplinary discussion, and with the patient's informed consent, surgery was performed awake under an interscalene block. We anticipated our patient would develop dyspnoea due to ipsilateral phrenic nerve palsy following the nerve block and therefore applied his own continuous positive airway pressure (CPAP) device intra‐operatively. We provided effective postoperative analgesia by using a continuous infusion of local anaesthetic through an interscalene peri‐neural catheter. Open shoulder surgery can be safely performed on patients with multiple co‐morbidities using carefully employed regional anaesthesia. The dyspnoea created by phrenic nerve block can be compensated for by applying CPAP.